2017
DOI: 10.1016/j.ultrasmedbio.2016.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Role of Bowel Ultrasound in the Diagnosis and Follow-up of Patients with Crohn's Disease

Abstract: Crohn's disease (CD) is an inflammatory chronic bowel disorder; it can involve the whole gastrointestinal tract, but its localization in the ileum or colon is most common. The reference standard for the diagnosis of CD is ileocolonoscopy with histologic assessment. The reference standard for the detection of any complications is surgery. However, imaging techniques have an important role both in the detection/localization of CD and in the follow-up of CD patients. In the last few years, the technical developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 46 publications
(81 reference statements)
0
20
0
Order By: Relevance
“…[2][3][4][5][6][7] This issue emphasizes the importance of a noninvasive and accurate diagnostic method in clinical practice. 3,8,9 None of the imaging modalities alone could qualify as gold standard for evaluation of all of the aspects of UC. [9][10][11] Ultrasonography in comparison with endoscopy is noninvasive, inexpensive, radiation free, easy to use, acceptable, repeatable and completely compatible with an ideal diagnostic method.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7] This issue emphasizes the importance of a noninvasive and accurate diagnostic method in clinical practice. 3,8,9 None of the imaging modalities alone could qualify as gold standard for evaluation of all of the aspects of UC. [9][10][11] Ultrasonography in comparison with endoscopy is noninvasive, inexpensive, radiation free, easy to use, acceptable, repeatable and completely compatible with an ideal diagnostic method.…”
Section: Introductionmentioning
confidence: 99%
“…Sonographic evaluation of the bowel has become one of the most valuable advancements of ultrasound in the past decade especially for patients with inflammatory bowel disease (IBD) who require frequent monitoring of their inflammatory activity due to its natural fluctuating course and the current use of biologic therapies [ 1 ]. Multiple studies have shown the accuracy of grayscale ultrasound (US) for determination of disease extent and activity [ 1 5 ]. Although, bowel wall thickness is the most reliable feature reflecting inflammation in the bowel wall, some patients with quiescent disease continue to show bowel wall thickening in the absence of active inflammation [ 5 7 ].…”
mentioning
confidence: 99%
“…Additional reports indicated that among the various radiological methods, BS and MRE are safer when evaluating bowel damage in CD [6]. Furthermore, we believe that another limitation of the current study is that it was designed as per-patient [7]. A previous meta-analysis including thirty-three studies suggested that the high sensitivity values detected in per-patient based studies should be explained with an overestimation of sensitivity values.…”
Section: Cross-sectional Evaluation Of Transmural Healing In Crohn's mentioning
confidence: 87%